2013
DOI: 10.18542/ragros.v4i1.1049
|View full text |Cite
|
Sign up to set email alerts
|

Ganho De Peso E Perfil Metabólico Sanguíneo De Cordeiros Alimentados Com Dietas Contendo Gordura Protegida

Abstract: RESUMO: O objetivo do trabalho foi avaliar a influência da gordura protegida sobre o ganho de peso e o perfil metabólico sanguíneo de cordeiros. Utilizou-se 14 cordeiros da raça Santa Inês do desmame até os 174 dias de idade, sendo utilizado o delineamento inteiramente casualizado com sete repetições (animais), dois tratamentos (dieta com e sem gordura protegida) e dois tempos de coleta de dados (início e final). As análises bioquímicas incluíram a determinação da glicose, ureia, triglicerídeos e colesterol. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…There was no effect (P>0.05) of supplementation on serum glucose. An opposite result was reported by Balaro et al (2012), who described an elevation of levels according to supplementation, and according to Van Soest (1994), who showed a consequent increase in the synthesis of propionate in the rumen, indicating higher consumption and availability of protein coming from the diet.…”
Section: Effects Of Supplementation In Native Ewesmentioning
confidence: 77%
“…There was no effect (P>0.05) of supplementation on serum glucose. An opposite result was reported by Balaro et al (2012), who described an elevation of levels according to supplementation, and according to Van Soest (1994), who showed a consequent increase in the synthesis of propionate in the rumen, indicating higher consumption and availability of protein coming from the diet.…”
Section: Effects Of Supplementation In Native Ewesmentioning
confidence: 77%
“…This result may have occurred because of the ether extract obtained from milk replacer. Balaro et al (2012) observed increased serum cholesterol levels in treatment with protected fat supplementation, probably by increased fat levels in the diet. Nunes et al (2010) observed increased cholesterol ratios in lambs as occurred an increase in inclusion of palm kernel cake in the diet.…”
Section: Discussionmentioning
confidence: 82%
“…Balaro et al. () observed increased serum cholesterol levels in treatment with protected fat supplementation, probably by increased fat levels in the diet. Nunes et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations